2016
DOI: 10.1002/ange.201609715
|View full text |Cite
|
Sign up to set email alerts
|

Azidoperfluoroalkanes: Synthesis and Application in Copper(I)‐Catalyzed Azide–Alkyne Cycloaddition

Abstract: We report an efficient and scalable synthesis of azidotrifluoromethane (CF 3 N 3 )a nd longer perfluorocarbonchain analogues (), which enables the direct insertion of CF 3 and perfluoroalkyl groups into triazole ring systems.T he azidoperfluoroalkaness how good reactivity with terminal alkynes in copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC), giving access to rare and stable N-perfluoroalkyl triazoles.A zidoperfluoroalkanes are thermally stable and the efficiency of their preparation should be attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The literature search revealed that low conversion and reductive deiodination are common problems for the Sonogashira coupling of 5-iodo-1,2,3triazolecarboxylates, 118 carboxamides, 119,120 nitriles, 121 and even 5-iodo-4-phenyl-triazoles. 122 It is particularly remarkable that for 5-iodotriazoles with an EWG at N 1 the Sonogashira reaction proceeded smoothly, 123 while for triazole with bulky EDG (ferrocenyl) the yields also were low. 124 The best and the simplest solution was found by David These conditions also worked perfectly for the crosscoupling of 4-ethynyl-5-iodotriazoles with acetylenes, providing unsymmetrically substituted enediynes 13a−g fused to 1,2,3-triazole ring in high yields (Scheme 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The literature search revealed that low conversion and reductive deiodination are common problems for the Sonogashira coupling of 5-iodo-1,2,3triazolecarboxylates, 118 carboxamides, 119,120 nitriles, 121 and even 5-iodo-4-phenyl-triazoles. 122 It is particularly remarkable that for 5-iodotriazoles with an EWG at N 1 the Sonogashira reaction proceeded smoothly, 123 while for triazole with bulky EDG (ferrocenyl) the yields also were low. 124 The best and the simplest solution was found by David These conditions also worked perfectly for the crosscoupling of 4-ethynyl-5-iodotriazoles with acetylenes, providing unsymmetrically substituted enediynes 13a−g fused to 1,2,3-triazole ring in high yields (Scheme 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Probing reactivity of azide 1 in [3 + 2] cycloaddition with aromatic or aliphatic terminal alkynes revealed that with 5 mol % of a Cu­(I) source (CuMeSal, copper­(I) 3-methylsalicylate), which was previously used in the click reaction with azidotrifluoromethane and other azidoperfluoroalkanes, the reaction was highly efficient and regiospecific at room temperature and afforded a range of N -bromotetrafluoroethyl-substituted 1,2,3-triazoles ( 2 ) in good to high yields (Table ). To demonstrate scalability of the reaction, triazole 2a was prepared on ca.…”
Section: Resultsmentioning
confidence: 99%
“…One such unique class of fluorinated building blocks, which has attracted attention recently, is α-fluorinated azides. , Fluorinated azidomethanes have witnessed a renaissance with the introduction of unknown azidofluoromethane, rebirth of known but forgotten and unused azidodifluoromethane, and new synthesis of azidotrifluoromethane and other azidoperfluoroalkanes, including highly synthetically useful azidopentafluoroethane . α-Fluorinated azidoethanes are synthetically accessible by azide addition to fluorinated ethylenes (such as tetrafluoroethylene or chlorotrifluoroethylene) and by quenching of the resulting fluorinated carbanion with a suitable electrophilic reagent (H + , CO 2 , ICl, Br 2 , electrophilic ester, or ArSCN) (Scheme A). Tetrafluoroethylene-containing azides were prepared from the corresponding bromides via organomagnesium compounds generated using turbo Grignard reagents (Scheme B). , Finally, 1-azido-2-iodo-1,1,2,2-tetrafluoroethane was prepared from sodium azide and 1,2-diiodotetrafluoroethane (Scheme C) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to perfluoroalkyl and perfluoroalkoxy groups, the chemistry of related perfluoroalkyl nitrogen substituents has been studied to a much lesser extent. Some synthetic strategies towards N ‐trifluoromethylamines and related N ‐perfluoroalkylnitrogen derivates have been developed in recent years [28–38] . Efficient strategies towards N , N ‐bis(perfluoroalkyl)nitrogen compounds remain scarce, presumably, because of the lack of suitable starting materials [18,39–40] .…”
Section: Figurementioning
confidence: 99%
“…Some synthetic strategies towards N ‐trifluoromethylamines and related N ‐perfluoroalkylnitrogen derivates have been developed in recent years. [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] Efficient strategies towards N , N ‐bis(perfluoroalkyl)nitrogen compounds remain scarce, presumably, because of the lack of suitable starting materials. [ 18 , 39 , 40 ] Especially the N , N ‐bis(trifluoromethyl)amino group is of interest as its organic derivatives are known to exhibit high stability, for example against acids and bases,[ 1 , 41 ] and because its potential as substituent in pharmaceuticals was demonstrated, earlier.…”
mentioning
confidence: 99%